2020
DOI: 10.1177/1120700020919943
|View full text |Cite
|
Sign up to set email alerts
|

Do trabecular metal cups achieve better results when compared to hemispherical porous titanium cups in acetabular revision surgery?

Abstract: Background: Trabecular metal (TM) cups were introduced in order to achieve better ingrowth and stability of the cup in acetabular revision surgery. As their use has evolved over time, we have queried whether TM cups would improve results in terms of the rate of aseptic loosening when compared to historical uncemented porous titanium cups used in revision surgery for acetabular bone loss in Hospital La Paz (Madrid, Spain). Methods: We retrospectively reviewed 197 acetabular revisions performed between 1991 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Comparing revision THA patients is complicated due to the differences in the indications for revision, bone defects, and implants used. Nevertheless, recent studies demonstrated similar implant survival rates and freedom from aseptic loosening when comparing trabecular metal to porous titanium cups in rTHA [22,23]. Similar to those studies, our cohort consisted of patients with moderate to severe bone loss (Paprosky IIA-III), and had an excellent 97.5% osteointegration rate according to the same criteria at 1-year follow up.…”
Section: Discussionmentioning
confidence: 70%
“…Comparing revision THA patients is complicated due to the differences in the indications for revision, bone defects, and implants used. Nevertheless, recent studies demonstrated similar implant survival rates and freedom from aseptic loosening when comparing trabecular metal to porous titanium cups in rTHA [22,23]. Similar to those studies, our cohort consisted of patients with moderate to severe bone loss (Paprosky IIA-III), and had an excellent 97.5% osteointegration rate according to the same criteria at 1-year follow up.…”
Section: Discussionmentioning
confidence: 70%
“…Finally, 67 articles were selected after full-text evaluation for eligibility. Table 2 provides a summary of the 67 rTHA studies (28,414 hips) showing the studies' characteristics and outcomes [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [82] , [83] , [84] ]. The stud...…”
Section: Resultsmentioning
confidence: 99%
“…Longer term follow-up is required before the technique is widely adapted. Ta augment 8 Chiarlone 2020 [ 26 ] Retrospective cohort Revision THA with Ta in severe bone defect eg, Paprosky III A–B 9 Acetabular aseptic loosening = 5 (55.6%) Osteolysis = 3 (33.3%) Second-stage reimplantation for PJI= 1 (11.1%) 35.3 ± 10.8 (minimum: 2-y) 3 (33.3%) 1 (11.1%) - NA Double porous Ta cup 9 Chacko 2020 [ 27 ] Retrospective cohort High friction TM sockets 146 ARMD = 55 (37.7%) Instability/Dislocation = 12 (8.2%) Psoas impingement = 3 (2.1%) Periprosthetic fracture = 11 (7.5%) Infection = 20 (13.7%) 43.5 (25-62) 6 (4.2%) 2 (1.37%) - NA TM acetabular component 10 Zhang 2020 [ 28 ] Retrospective cohort Double-TM cups for revision of complex acetabular defects 18 hip (18 patients) Aseptic loosening (100%) 61.0 (IQR: 56.0-65.8) 0 (0%) 0 (0%) NA Acetabular revision with double- TM cups with or without impacting bone grafting are practical and acceptable treatment Double-TM cups 11 Cruz-Pardos 2020 [ 29 ] Retrospective cohort Titanium and TM cups in revision surgery for acetabular bone loss 197 8.1 y (1-15) There was no significant difference in re-revision due to aseptic loosening or radiological loosening between titanium and TM cups in revision surgery for acetabular bone loss. TM cup Group1: TM cup 116 Aseptic cup loosening = 91 (78.4%) Revision due to infection (2nd stage) = 3 (2.6%) Polyethylene wear = 6 (5.2%) Other = 16 (13.8%) 5.4 ± 3.1 y 5 (4.3%), P = .54 0 (0%) 0 (0%) Group2: Ti cup 81...…”
Section: Resultsmentioning
confidence: 99%
“…1 of the most common reasons for revision is instability of the acetabular component of THA. 1,3 As THA is performed at younger ages, there is also a need for earlier revision procedures and the possibility of further revisions during each patient's life is increasing. According to data from the Norwegian Arthroplasty Registry, revision THAs have a significantly higher rate of failure compared to primary THAs, with 27.9% of revision procedures requiring re-revision after 10 years comparing to 11.4% of primary THAs.…”
Section: Introductionmentioning
confidence: 99%
“…4 The goal of the revision surgery is to achieve a stable acetabular component with good bone stock and the best possible biomechanical conditions to provide good function and longevity of the endoprosthesis. 3 Placing the acetabular component as close as possible to the ideal center of rotation is one of the major tasks in order to accomplish these goals. 5,6 Depending on the size and location of acetabular bone defects there are various surgical techniques and implants available for acetabular reconstruction.…”
Section: Introductionmentioning
confidence: 99%